Influence of Adding Different Fillers on Polyethylene Properties - Abdulla Abd Al-shakoor; Ame’r H. Majeed; Saba A. Ghani (Tikrit Journal of Engineering Sciences, 2006)
The aim of this study was focused on the improvement of pouring, mechanical and thermal properties of high density polyethylene using chemically treated kawaline as a filler which is composed of 10% carbamide and 90% kawaline. A composed had been made among the new filler (kawaline-carbamide), alumina and the pure kawaline in improving the latter properties of polyethylene. It was found that all the mentioned properties affect deeply by filler type and its content. Also it was found that the suitable filler is alumina and kawaline –carrbamide in less performance.